2021
DOI: 10.3390/jof7080624
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 Induces Major Phosphorylation Changes in Critical Regulators of Signal Transduction, Gene Expression, Metabolism and Developmental Networks in Aspergillus nidulans

Abstract: Reactive oxygen species (ROS) regulate several aspects of cell physiology in filamentous fungi including the antioxidant response and development. However, little is known about the signaling pathways involved in these processes. Here, we report Aspergillus nidulans global phosphoproteome during mycelial growth and show that under these conditions, H2O2 induces major changes in protein phosphorylation. Among the 1964 phosphoproteins we identified, H2O2 induced the phosphorylation of 131 proteins at one or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 222 publications
(334 reference statements)
0
13
0
Order By: Relevance
“…brlA and the other two genes in the central regulatory pathway ( abaA and wetA ) were also found to be regulated by SakA, a member of the stress-activated MAPK (SAPK) pathway in T. marneffei [ 77 ]. In a recent work analyzing the phosphoproteome response to H 2 O 2 in A. nidulans , Carrasco-Navarro and Aguirre [ 78 ] found that StuA, a protein required for proper expression of brlA , was specifically phosphorylated in the H 2 O 2 -condition, which suggests that phosphorylation plays also a role in the oxidative stress-mediated regulation of conidiation; interestingly, NapA was also phosphorylated in the H 2 O 2 -condition. In this work we describe for the first time a direct regulation of a gene in the conidiation central regulatory pathway, the brlA gene, by an oxidative stress defense protein; PcYap1 binds to a TTACTAA sequence in the brlA gene promoter and upregulates expression of this gene, thus triggering conidiation.…”
Section: Discussionmentioning
confidence: 99%
“…brlA and the other two genes in the central regulatory pathway ( abaA and wetA ) were also found to be regulated by SakA, a member of the stress-activated MAPK (SAPK) pathway in T. marneffei [ 77 ]. In a recent work analyzing the phosphoproteome response to H 2 O 2 in A. nidulans , Carrasco-Navarro and Aguirre [ 78 ] found that StuA, a protein required for proper expression of brlA , was specifically phosphorylated in the H 2 O 2 -condition, which suggests that phosphorylation plays also a role in the oxidative stress-mediated regulation of conidiation; interestingly, NapA was also phosphorylated in the H 2 O 2 -condition. In this work we describe for the first time a direct regulation of a gene in the conidiation central regulatory pathway, the brlA gene, by an oxidative stress defense protein; PcYap1 binds to a TTACTAA sequence in the brlA gene promoter and upregulates expression of this gene, thus triggering conidiation.…”
Section: Discussionmentioning
confidence: 99%
“…The serine–threonine kinase is the target of rapamycin (TOR) and regulates cell growth and stress signalling in eukaryotes. A single TOR kinase TorA was characterized in A. nidulans , which contained four phosphosites during growth and three of them were dephosphorylated under oxidative stress (Carrasco‐Navarro and Aguirre, 2021). The TOR signalling pathway regulates phosphorylation of the Ser/Thr kinase Sch9, a substrate of TOR, to control fungal development and mediate multiple stresses responses as well as mycotoxin synthesis in some fungal pathogens (Gu et al ., 2015; Alves de Castro et al ., 2016).…”
Section: Post‐translational Regulation Of Secondary Metabolite Biosyn...mentioning
confidence: 99%
“…In A. nidulans , over 1964 proteins were characterized phosphorylated, among which the reversible phosphorylated state of 131 proteins were influenced by the oxidative stress agent hydrogen peroxide (H 2 O 2 ) (Carrasco‐Navarro and Aguirre, 2021). Additionally, the phosphorylation of critical components of MAPK, and TOR signalling as well as the proteins that involved in the regulation of primary and secondary metabolism were found affected by H 2 O 2 in A. nidulans .…”
Section: Post‐translational Regulation Of Secondary Metabolite Biosyn...mentioning
confidence: 99%
“…H 2 O 2 is considered to be the most relevant ROS in redox biology [ 10 ]. Indeed, in the fungus Aspergillus nidulans , H 2 O 2 activates the MAPKs SakA, MpkC [ 8 , 11 , 12 ], MpkA and MpkB [ 13 ], and changes the phosphorylation patterns of multiple other proteins involved in signal transduction, gene expression, metabolism and development [ 13 ]. SakA mediates the nuclear localization of its substrate SrkA, and when SakA is not present, H 2 O 2 induces SrkA mitochondrial localization [ 14 ].…”
Section: Introductionmentioning
confidence: 99%